From the Phoenician abjad to the Greek alphabet and the Palaeo-Hispanic semi-syllabaries: Similarities and differences in the adaptation process (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2024)
This paper makes a comparative study of the adaptation of the Phoenician abjad to the Greek alphabet in the 9th century BC and to the Palaeo-Hispanic semi-syllabaries from the 7th century BC onwards, seeking arguments for the discussion as to whether the Hispanic adaptation underwent some Hellenic intermediation. Just as we know that the Anatolian or Italic alphabets (used for different languages), are not direct adaptations of the Phoenician abjad, but have passed through a "Greek" filter, in the case of the Iberian Peninsula, researchers have traditionally considered that the direct inspiration in a Phoenician model is evident but have been hesitant about a possible interference of a Greek model, positioning themselves in favour or against this possibility. To this end, the parallel processes of generating new letters for sounds not reflected in the Phoenician script are analysed in detail, and the extent to which it is plausible that they respond to independent processes is assessed, leading to the conclusion that a hypothetical Greek intermediation is not demonstrable and is in fact unlikely.
Keywords: Phoenician abjad; Greek alphabet; Paleo-Hispanic semi-syllabaries; history of writing; acrophony; Palaeo-Hispanic languages